Australian Trends in Procedural Characteristics and Outcomes in Patients Undergoing Percutaneous Coronary Intervention for ST-Elevation Myocardial Infarction - Biswas, S.; Duffy, S.; Lefkovits, J.; Andrianopoulos, N.; Brennan, Angela; Walton, A.; Chan, W.; Noaman, S.; Shaw, J.; Dawson, L.; Ajani, A.; Clark, D.; et al. (Excerpta Medica, Inc, 2017)
Over the last decade, systems of care for ST-elevation myocardial infarction (STEMI) have evolved to try to improve outcomes and timely access to percutaneous coronary intervention (PCI). There have also been advances in PCI techniques and adjunctive pharmacotherapies. In this study, we sought to determine temporal changes in practices and clinical outcomes of PCI in patients with STEMI. We prospectively collected data on 8,412 consecutive patients undergoing PCI for STEMI between 2005 and 2016 in the multicenter Melbourne Interventional Group registry. Data were divided by procedure year for trends analysis. The primary end point was 30-day mortality. Patient demographics and comorbidities including smoking and diabetes have remained stable. The volume of primary PCI performed within 12 hours of symptom onset has significantly risen (65.7% to 80.1%, p < 0.01). The proportion of patients achieving the recommended door-to-balloon time =90 minutes has also risen (37.6% to 59.0%, p < 0.01). Patient complexity has also increased with more patients after out-of-hospital cardiac arrest with STEMI now being treated with PCI (2.6% to 9.1%, p < 0.01). A shift from mainly femoral to radial access and from bare-metal to drug-eluting stent use was seen. Glycoprotein IIb/IIIa inhibitors are being used less frequently with increasing use of newer antiplatelet agents. Thirty-day mortality has remained low throughout the study period at 6.5% overall. In conclusion, although timely access to primary PCI has improved, mortality rates have remained unchanged, but remain low and compare favorably with international data. Australian PCI practice has overall evolved in response to evidence and emergence of new adjunctive device and pharmacotherapies.